AN INVESTIGATION INTO THE DEVELOPMENT OF CRITERIA FOR SOUTH AFRICAN SMALL MEDIUM ENTERPRISES (SME) BRANDS TO EMPLOY WHEN COLLABORATING WITH RELEVANT INFLUENCERS TO REINFORCE BRAND ALIGNMENT - Mashego, Tholoane (The IIE, 2022)
In these times when technology is at our fingertips and content is shared at a much faster rate than ever before, we are seeing an increase in brand influencer collaboration campaigns. This study examines the extent to which collaboration between relevant influencers and brands can aid in the development of a criterion that can be used to reinforce brand alignment by SMEs in South Africa and even any size brand. Through eWOM, social media influencers are gaining control of the Internet through their exceptional work and presence. Their opinions have a sizable influence on people, impacting on brands and buying decisions. They can be classified as a contemporary phenomenon, as their collaboration with marketing agencies has increased significantly in recent years. More and more people are subscribing to these influencers' content in order to avoid missing out on content the influencers share. Brands seek mentions, reviews, and recommendations from such influencers. Even though influencer marketing is a relatively new strategy, it remains a viable option for marketers willing to think creatively and develop relationships with their target market. The study's objective is to establish a set of criteria that South African SME brands can use to collaborate with relevant influencers to strengthen their brand alignment. Participants in this study interacted with brand managers at corporates, brand influencer agencies, and influencers. The research findings concluded that while there is no industry-wide standard for creating relevant brand influencer collaborations, there were several highly similar elements that brands, and agencies used to engage in effective relevant brand influencer collaborations. These elements can be used in additional future studies to develop a criterion that SMEs can use in the absence of affordable influencer marketing through agencies and also participate in the influencer space to grow their brand.
Keywords: Social media; Digital marketing; Customer behaviour; Branding